WAYS TO INCREASE QUALITY OF PRODUCTS AT THE BAR STOCK WIRE ROLL MILL 150 IN OJSC «BSW» – MANAGEMENT COMPANY OF HOLDING «BMC» - I. A. Zuyeu,; Yu. L. Bobarikin (Литьë и металлургия)
The issues of perfecting of calibrating of rolling rolls of bar stock wire roll mill 150 to increase in accuracy of the geometrical sizes of the rolled profile is considered.